Assessment of marine warming in Indonesia: a case study off the coast of West Sumatra. Issue 1 (March 2021) - Azis Ismail, M F; Gerhaneu, N Y; Yulihastin, E; Ratnawati, H I; Purwandana, A
Abstract: Over recent decades, warming events in the tropical Indian Ocean (IO) have been documented in both the western and eastern IO. However, the manifestation of marine warming events in the Indonesian waters is still lacking in information. This paper presents the first case study of long-term warming events and short-term extreme warming events off the coast of West Sumatra using Sea Surface Temperature (SST) data covering 37 years (1982-2018). A statistical climate toolbox is applied to quantify the marine warming rates, including Marine Heatwaves (MHWs) identification. Decadal trends in marine warming are positive across the study region indicate significant warming rates with the average value of about 0.15°C decade −1 . In line with the long-term marine warming, MHW events off West Sumatra has been revealed to be increasing in its occurrences, duration, and intensity. Much of this significant increase in MHW properties has occurred during the period 2015-2018. The MHW events off West Sumatra appear to be influenced by El Niño Southern Oscillation (ENSO), particularly during strong El Niño and La Niña periods. These marine warmings trend and MHW events have never been documented and quantified before in the waters around West Sumatra.